Handbook of stability in structural engineering - Perelmuter, Anatoly V. (World Scientific, 2013)
Handbook of Mechanical Stability in Engineering (In 3 Volumes) is a systematic presentation of mathematical statements and methods of solution for problems of structural stability. It also presents a connection between the solutions of the problems and the actual design practice. This comprehensive multi-volume set with applications in Applied Mechanics, Structural, Civil and Mechanical Engineering and Applied Mathematics is useful for research engineers and developers of CAD/CAE software who investigate the stability of equilibrium of mechanical systems; practical engineers who use the software tools in their daily work and are interested in knowing more about the theoretical foundations of the strength analysis; and for advanced students and faculty of university departments where strength-related subjects of civil and mechanical engineering are taught.